Part of small dams in runoff water management and in erosion control. A study in the Middle East and North Africa Region (NEMA) - (:unkn) unknown (My University, 2006)
In the beginning of the 1990s, the construction of small dams seemed to take precedence over the policy of large hydraulic works that was popular in the Middle East and North Africa Region (NEMA) during the second part of the 20th century. Nowadays, all countries of NEMA region are involved in a policy of constructing small and middle size dams. These dams appear as very specific structures designed not only to mobilize the surface water resources but also to control runoff and sediment fluxes. They are built for protecting downstream infrastructures and particularly rapid sedimentation of large dams. They integrated rural development by offering a fair distribution of water in the countryside, limiting disruptions in the social order like massive expropriation, and displacement of infrastructure or lodging. Using the results of multi-disciplinary research carried out in two countries in northern Africa (Morocco and Tunisia), and two countries in the Near East (Lebanon and Syria), this paper endeavours to show the position of small dams in the mobilization and management of water and soil resources in the semi-arid Mediterranean zones. It describes how the development of small dams has followed different directions and objectives in each country. For example, the goal of large dam protection is more prevalent in northern Africa than in the Middle East. The prospect of protecting the conservation works and structures are studied using a model of estimation and simulation of sediment transport and yields. These studies allowed the better understanding of the erosion phenomena of and siltation. The stakes of integrated development around hill reservoirs are presented through the progress of irrigation and through environmental impacts as the recharge of the water table.
Keywords: African Research